EVALUATION OF ACADEMIC LIBRARY WEB SITES IN MALAYSIA - Lee, K.H.; Teh, K.H. (Malaysian Journal of Library and Information Science, 2000)
This study evaluates the content and design of academic library Web sites in Malaysia and uses a mixed-method approach that combines both quantitative and qualitative analyses of academic library Web sites evaluation. A total of twelve library Web sites of public and private institutions of higher learning were selected for evaluation. The findings reveal that the academic libraries in Malaysia generally have set up well-designed and useful Web sites. A few academic library Web sites, however, have very simple and basic features. Overall, they fall short of expectations as virtual expressions of the quality levels of academic libraries.